2012
DOI: 10.1177/0361684312451098
|View full text |Cite
|
Sign up to set email alerts
|

Not All Nonlabelers Are Created Equal

Abstract: Past research regarding feminist identity has revealed that a significant number of women endorse feminist attitudes yet reject a feminist identity. In the current study, we sought to examine whether these nonlabeling women fall into two distinct groups: (a) one that falls on the same ideological continuum of their feminist peers and (b) the other that represents an attitudinally unique group of women characterized by their neoliberal beliefs that prioritize individual merit as the sole determinant of success.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 54 publications
(120 reference statements)
1
14
0
Order By: Relevance
“…Thus, we expect that it is through the enhanced perception of personal control that neoliberal ideology leads to a greater perception that the system is just, because it entails that upward mobility and happiness are possible within the system, as long as one exercises one's control in putting the sufficient effort (Osborne et al, 2019). Because targeting and aiming for structural changes is perceived as illegitimate, and because one should not be preoccupied by group-level issues, we also hypothesize that neoliberal ideology should be negatively associated to CA, notably through its effect on politicized identity (Simon & Klandermans, 2001; and see Bonnot, Redersdorff, Girerd & Verniers, 2020;Fitz, Zucker & Bay-Cheng, 2012. This hypothesis will be tested in two correlational studies conducted in the context of the YV movement.…”
Section: Neoliberal Ideology: a Barrier To Engagement In Camentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, we expect that it is through the enhanced perception of personal control that neoliberal ideology leads to a greater perception that the system is just, because it entails that upward mobility and happiness are possible within the system, as long as one exercises one's control in putting the sufficient effort (Osborne et al, 2019). Because targeting and aiming for structural changes is perceived as illegitimate, and because one should not be preoccupied by group-level issues, we also hypothesize that neoliberal ideology should be negatively associated to CA, notably through its effect on politicized identity (Simon & Klandermans, 2001; and see Bonnot, Redersdorff, Girerd & Verniers, 2020;Fitz, Zucker & Bay-Cheng, 2012. This hypothesis will be tested in two correlational studies conducted in the context of the YV movement.…”
Section: Neoliberal Ideology: a Barrier To Engagement In Camentioning
confidence: 89%
“…Exploratory analysis on politicized identities and neoliberal ideology Finally, and interestingly, YV identification positively correlated with ecologist and feminist identification, two system-challenging identities (see Table 6), which again indicates that the YV identity reflects a system-challenging stance. Moreover, the more people endorsed neoliberal ideology, the less likely they were to identify as YVs, but also as ecologists and feminists (see also Fitz et al, 2012;…”
Section: Model Testingmentioning
confidence: 99%
“…Another open question concerns our definition of feminist identity. Researchers have defined feminism in a variety of ways, noting that there may be important differences between self-labeling, public labeling, beliefs, and behaviors (e.g., Fitz, Zucker, & Bay-Cheng, 2012; Yoder, Snell, & Tobias, 2012; Yoder, Tobias, & Snell, 2011). Although a reanalysis of the present effects suggests that gender-equality attitudes and implicit and explicit attitudes toward prototypes similarly predict each of the items in the outcome measure (“I consider myself a feminist”—self-identification; “I identify myself as a feminist to other people”—public identification; “Feminist values and principles are important to me”—a belief; “I support the goals of the feminist movement”—a belief; Szymanski, 2004), future studies might consider using measures that assess a variety of forms of identification with several items (see Fitz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, feminist identity cannot be replaced by, or reduced to, feminist beliefs (i.e., beliefs about gender equality). Although feminist identity has been conflated with feminist beliefs (Enns, 1997), equality beliefs alone do not necessarily result in willingness to call oneself a feminist (Fitz, Zucker, & Bay-Cheng, 2012;Williams & Wittig, 1997;Zucker & Bay-Cheng, 2010). Furthermore, consistent with social identity theory (Tajfel & Turner, 1979), identity confers benefits independent of beliefs; feminist identity is associated with outcomes such as charity donations and body satisfaction over and above, or better than, beliefs in accord with feminism (Murnen & Smolak, 2009;Redford et al, 2018;Yoder et al, 2011).…”
Section: Why Is Feminist Identity Important?mentioning
confidence: 99%
“…A recent study (Hoskin, Jenson, & Blair, 2017) found that people who defined feminism using intersectional principles were more likely to identify as feminists. And some individuals with egalitarian beliefs reject feminism for the opposite reason: Non-labelers who endorse neoliberal beliefs of individualism, competition, and meritocracy may find that feminism focuses too much on structural forces and collective identity (Fitz et al, 2012). Thus, while feminist identity appears deeply rooted in a complex social system, this complexity is not often explored in research on feminist identity.…”
Section: Feminist Identity and Feminist Prototypesmentioning
confidence: 99%